Strength and Fracture Analysis of Brittle Photoelastic Material. Static And Dynamic Tests. - Kruszka, L.; Nowacki, W.K.; Wolna, M. (Engineering Transactions, 1992)
Results of static and dynamic uniaxial compression tests on brittle transparent model material are presented. Multiple static experiments were made with the use of ultrasonic measurements, acoustic emission, photoelasticity and photographic registration of changes in the studied specimens. In this way comprehensive information on the mechanics of defects and fracture of the material was collected. In the dynamic investigations a standard Hopkinson bar device was used. Static and dynamic characteristics were compared, short-term strengths and mechanisms of cracking and fracture were studied, taking into account slenderness of testpieces.